2009
DOI: 10.1002/ijc.24930
|View full text |Cite
|
Sign up to set email alerts
|

Salivary gland and nasopharyngeal cancers in individuals with acquired immunodeficiency syndrome in United States

Abstract: Individuals with acquired immunodeficiency syndrome (AIDS) manifest an increased risk of cancer, particularly cancers caused by oncogenic viruses. Because some salivary gland and nasopharyngeal cancers are associated with Epstein Barr virus, the impact of AIDS on these cancers needs further evaluation. We used linked U.S. AIDS and cancer registry data (N 5 519,934 people with AIDS) to derive standardized incidence ratios (SIRs) comparing risk of salivary gland and nasopharyngeal cancers to the general populati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
0
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 31 publications
(25 citation statements)
references
References 52 publications
0
24
0
1
Order By: Relevance
“…[43][44][45] The status of the immune system plays a role for the development of NPC. For example, in a comprehensive study, Shebl et al 46 showed that AIDS patients have a moderately increased risk compared to the normal population (standardized incidence risk of 2.0) for NPC (both K-and NK-NPC). The fact that the salivary gland analog to NK-NPC, lymphoepithelial carcinoma, is significantly more common in the same patient group is somewhat puzzling.…”
Section: Etiology and Pathogenesismentioning
confidence: 97%
See 1 more Smart Citation
“…[43][44][45] The status of the immune system plays a role for the development of NPC. For example, in a comprehensive study, Shebl et al 46 showed that AIDS patients have a moderately increased risk compared to the normal population (standardized incidence risk of 2.0) for NPC (both K-and NK-NPC). The fact that the salivary gland analog to NK-NPC, lymphoepithelial carcinoma, is significantly more common in the same patient group is somewhat puzzling.…”
Section: Etiology and Pathogenesismentioning
confidence: 97%
“…The fact that the salivary gland analog to NK-NPC, lymphoepithelial carcinoma, is significantly more common in the same patient group is somewhat puzzling. 46 There is increasing evidence that oncogenic ("high risk") human papillomavirus (HPV) plays a significant role in a subset of NPC, especially in non-endemic regions. This is discussed further below.…”
Section: Etiology and Pathogenesismentioning
confidence: 99%
“…In the U.S., myasthenia gravis may be more common in blacks than whites (12), mirroring the pattern for thymoma. Also of interest, Asians have a relatively high risk for developing cancers of the nasopharynx and salivary gland, which (like thymoma) derive from the embryonic foregut (13). The reasons for this clustering of cancer risk among Asians are unclear.…”
Section: Descriptive Epidemiology Of Thymomamentioning
confidence: 99%
“…A few studies have suggested that radiation exposure (e.g., radiation treatment to the head and neck area), certain workplace exposures (e.g., nickel alloy dust, silica dust, asbestos, mining, and rubber products manufacturing), tobacco use, alcohol consumption, diets low in vegetables and high in animal fat, and heavy cell phone use are possible risk factors [1, 5]. Also implicated has been a previous history of cancer [6] and exposure to certain viruses including HIV [7], Epstein Barr [8], and possibly HPV [9]. …”
Section: Introductionmentioning
confidence: 99%